Operational Drilling Risk Analysis Using Failure Mode and Effect Analysis (FMEA) Method in an Oil and Gas Company - Kolopaking, Steven Raynard; Gunarta, I Ketut (Direktorat Riset dan Pengabdian Masyarakat (DRPM), ITS, 2024)
Drilling operations in the oil and gas industry are among the riskiest activities, with high potential for injury and environmental damage. Therefore, thorough risk analysis and assessment are crucial to minimize these risks. This research aims to reassess and prioritize operational risks, recommending mitigation actions using Failure Modes and Effects Analysis (FMEA) and ISO 31000:2018 standards. The study involves risk identification through expert interviews, resulting in the identification of 364 combined risks, including failure modes, probable causes, and effects. Using the Risk Priority Number (RPN), risks were prioritized, and responses were categorized into mitigate (60%), transfer (25%), accept (11%), and avoid (4%). This approach enables the company to manage risks more effectively, ensuring safety and operational efficiency. The findings indicate that proper risk prioritization and response can significantly reduce potential damage. However, this research highlights the need for a more comprehensive analysis, including financial risk assessments, to maximize the effectiveness of risk management strategies. The results provide valuable insights for improving the company’s risk management framework, contributing to the overall safety and sustainability of drilling operations. Future research should focus on integrating financial risk evaluations to enhance the robustness of the risk management process.